2006
DOI: 10.1080/02724980543000204
|View full text |Cite
|
Sign up to set email alerts
|

Snakes, spiders, guns, and syringes: How specific are evolutionary constraints on the detection of threatening stimuli?

Abstract: In three experiments, the efficiency in detecting fear-relevant and fear-irrelevant visual stimuli are compared. A visual search paradigm is used where participants are presented with matrices of different sizes (4 objects/9 objects) and must determine whether all objects are taken from the same category or whether there is a discrepant one. Results from all experiments were consistent with the threat-superiority effect. Participants were quicker when the target was threatening than when it was not. Other indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
188
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 211 publications
(214 citation statements)
references
References 42 publications
23
188
2
1
Order By: Relevance
“…Öhman & Mineka, 2001). Consistent with this, previous work has shown that a single negatively valenced stimulus appears to capture or guide attention more strongly than a positively valenced target (Eastwood et al, 2001;Fox et al, 2000;Blanchette, 2006;Lipp et al, 2004). Furthermore, once attended, it might be more difficult to disengage attention from a negative stimulus than from a positive stimulus (e.g., Fox et al, 2001Fox et al, , 2002Georgiou et al, 2005;Fenske & Eastwood, 2003).…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…Öhman & Mineka, 2001). Consistent with this, previous work has shown that a single negatively valenced stimulus appears to capture or guide attention more strongly than a positively valenced target (Eastwood et al, 2001;Fox et al, 2000;Blanchette, 2006;Lipp et al, 2004). Furthermore, once attended, it might be more difficult to disengage attention from a negative stimulus than from a positive stimulus (e.g., Fox et al, 2001Fox et al, , 2002Georgiou et al, 2005;Fenske & Eastwood, 2003).…”
Section: Discussionsupporting
confidence: 65%
“…As discussed above, previous visual search studies (Eastwood et al, 2001;Fox et al, 2000;Blanchette, 2006;Lipp et al, 2004;Blagrove & Watson, 2010) have found that negatively valenced targets can attract/guide attention more efficiently than positive targets.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Hasonlóképpen Blanchette (2006) is a klasszikus vizuális kereséses eljárást (Öhman, Flykt és Esteves, 2001) alkalmazva a kígyók, pókok és semleges ingerek mellett modern fenyegető ingereket is használt (fegyverek és injekciós tűk) vizsgálatában. A résztvevők gyorsabban találták meg a célingert, mikor az fenyegető volt, mint mikor nem.…”
Section: Hasonló áLláspontot Képvisel Fox Griggs éS Mouchlianitisunclassified